Oreoglanis brevicula, a new species of rheophilic catfish from Laos (Actinopterygii: Sisoridae) - Ng, Heok Hee; Kottelat, Maurice (Ichthyological research, 2025)
Oreoglanis brevicula, a new species of sisorid catfish, is described from a single specimen collected in northern Laos. It belongs to the Oreoglanis delacouri group in lacking a distinct median notch on the posterior margin of the lower lip and can be distinguished from congeners by the following combination of characters: nasal barbel length 31% of head length, pectoral fin not reaching pelvic-fin origin, body depth at anus 10% of standard length (SL), adipose fin with base 36% SL and posteriorly separate from dorsal procurrent caudal-fin rays, caudal peduncle length 19% SL, caudal peduncle depth 4% SL (= 4.3 times in peduncle length), lunate caudal fin, and 42 vertebrae.